Significance and prospects of recreational forest management in the territorial recreational forest-cultural system of the Northwestern Azov coastal area - Яценко, Анастасія (Human Geography Journal, 2016)
The article deals with perspective directions of development and optimization of recreational forest management in northwestern Azov coastal area. The forest-cultural landscapes of the studied area have powerful natural resource potential that should be used for tourism and recreation. In the method of determining the recreational potential have been studied aesthetic properties of forests, pedestrian access areas, sanitary properties of planted forests and recreational sustainability. Studies of the recreational potential of forest-cultural landscapes have shown that forests are the average recreational assessments, due to the artificial origin of planted forests. One of the most rational methods of organization of recreation process in forest is a functional-recreational zoning of a forest landscape. This system of organization will allow recreants to choose the most appropriate form of recreation. The article lists the main recreational areas, such as area of natural reserves, recreational area and r<a title="Показать примеры употребления" href="http://www.lingvo.ua/ru/Search/Translate/GlossaryItemExtraInfo?text=%d0%b7%d0%be%d0%bd%d0%b0%20%d0%be%d1%82%d0%b4%d1%8b%d1%85%d0%b0&translation=recreation%20area&srcLang=ru&destLang=en">ecreation area for a long period of rest, zone of short active holiday, area of green tourism and area of recreational needs satisfaction. For further the rational use of forest-cultural landscapes for recreational purposes requires the implementation of special forestry activities that take into account the tough growing conditions of the forest.